Quality of life measured 12 months postoperatively in subjects who had an anterior neck fusion - De Jonge, Louise (My University, 2010)
The cervical spine is subjected to wear and tear as well as trauma. This increases the occurrence of degeneration of intervertebral discs and facet joints. Degeneration will result in loss of disc height and the formation of osteophytes on adjacent vertebrae. Nerve roots can be irritated or compressed by this pathology and patients can possibly develop neurological signs and symptoms as well as pain. An anterior neck fusion is a surgical procedure that is frequently used to manage cervical pathologies such as degeneration, spinal stenosis, disc herniation, or trauma. Cervical pathologies can become severe and neural compression may develop. Compression of neural components can present with symptoms such as muscle weakness, numbness, tingling or radicular pain. The main aim of the surgery is to decompress the neural structures, permanently stabilize the vertebrae, to maintain a cervical lordosis and to hold an anatomical disc space. Chronic spinal disorders, including cervical and lumbar conditions, are considered the most expensive benign condition to manage. Previous research demonstrated poor functional outcomes especially in the lumbar area. Little evidence is available regarding the functional outcomes of patients after anterior neck fusion surgery. The aim of this study was to investigate the levels of pain and the quality of life experienced by patients who had an anterior neck fusion one year ago. Methods A cross – sectional survey was conducted. Neurosurgeons in the Johannesburg region were contacted telephonically to establish whether they performed anterior neck fusion surgery. Potential subjects were then identified and contacted to establish whether they suited the inclusion criteria for the study. Pain was assessed using the Visual Analogue Scale. The Neck Disability Index, Fear Avoidance Beliefs and Short Form-36 questionnaires were completed to determine the levels of dysfunction, anxiety and depression as well as health related quality of life in subjects who had an anterior neck fusion one year ago. The quality of life of these subjects was then compared to that of a healthy baseline group. Results and Discussion Forty-two (n = 42) subjects were telephonically identified from the neurosurgeons’ records. Thirty-five (n = 35) subjects met the inclusion criteria and participated in the study. Twenty-six subjects were female (n = 26) with an average age of 54 years and nine (n = 9) were male with an average age of 53 years. The demographic questionnaire demonstrated a high prevalence v for the use of pain- and anti-inflammatory medication (81.3%). According to the demographic questionnaire, the subjects received on average six physiotherapy treatments postoperatively. Most of the subjects (n = 22) demonstrated pain over the upper shoulder area as well as posterior regions of the neck on the body chart. At the time of assessment, the subjects indicated their level of pain using a VAS scale and had an average score of 35.48mm (SD ± 24.11) which indicated a low level of pain. Results obtained from the NDI questionnaire indicated that the subjects had moderate disability one year postoperatively. The mean score on the NDI for subjects was 31.10 (SD ± 11.96). Subjects did not demonstrate high scores on the FABQ and had a mean score of 54.09 (SD ± 0.99). There were no significant differences between the male and female groups for the FABQ. On the SF-36, the subjects had a moderate reduction in mental health components of QoL [MCS = 42.19 (SD ± 13.31)] as well as the physical health components of QoL [PCS = 46.78 (9.44)]. QoL of these subjects was compared to a baseline group. Results showed a statistically significant difference between the groups for all eight domains (p- values ranged between 0.0001 and 0.012). The mental health component score (MCS) was not significantly different between the groups but subjects with anterior neck fusion had a significantly lower score on the physical health component (PCS) than the baseline group (p = 0.001). Conclusion This paper concluded that subjects who had an anterior neck fusion 12 months ago still suffered from low levels of pain and moderate dysfunction. They reported low levels of QoL related to physical health one year postoperatively.
MSc Physiotherapy, Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: spinal fusion; QoL